Comparison of the dental anomaly frequency in patients with and without mandibular second premolar agenesis - Kenan Cantekin; Mevlut Celikoglu (Elsevier, 2015)
Background/purpose: There is remarkably little information in the literature comparing the prevalence of dental anomalies associated with mandibular second premolar (MP2) agenesis with control groups. The aim of the present study was to investigate the frequency of dental anomalies associated with agenesis of the MP2, and to compare the results with control groups. Materials and methods: A total of 4812 panoramic radiographs (also called orthopantograms, OPGs) and dental casts were used to assess the presence of MP2 agenesis and 245 patients (age range: 11-18 years) with MP2 agenesis were included in the study. OPGs and dental casts were used to assess the presence of the following dental anomalies: (1) tooth agenesis excluding third molars; (2) third molar agenesis; (3) supernumerary teeth; (4) taurodontism of permanent teeth; and (5) microdontia of maxillary lateral incisors. Results: The prevalence of MP2 agenesis was found to be 5.1% (245/4812) with no statistical sex difference (P = 0.209). The prevalence of tooth agenesis excluding the third molars (P < 0.05), third molar agenesis (P < 0.05), taurodontism (P < 0.001), and microdontia of maxillary lateral incisors (P < 0.05) were significantly greater in patients with agenesis of MP2. Conclusion: Tooth agenesis, microdontia of maxillary lateral incisor, and taurodontism are frequently associated with agenesis of MP2 as compared with a well matched control group and different populations.